2007
DOI: 10.1523/jneurosci.5330-06.2007
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Mild Stress during Gestation Worsens Neonatal Brain Lesions in Mice

Abstract: Cerebral palsy remains a public health priority. Recognition of factors of susceptibility to perinatal brain lesions is key for the prevention of cerebral palsy. In most cases, the pathophysiology of these lesions is thought to involve prior exposure to predisposing factors that make the developing brain more vulnerable to perinatal events. The present study tested the hypothesis that exposure to chronic minimal stress throughout gestation would sensitize the offspring to neonatal excitotoxic brain lesions, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 50 publications
(49 reference statements)
2
32
0
1
Order By: Relevance
“…We speculate that stress exposure in the immature brain has an adverse effect on cerebral injury and/or development such that reduction in stress via MITP-type intervention enhances cerebral white matter development as measured by ADC and anisotropy. This is supported by recent experimental data in the immature brain that has emphasized the capacity of mild chronic stress to worsen brain injury (29). In addition, stress exposure increases hypothalamic-pituitary-adrenal (HPA) hormonal reactions resulting in altered cerebral white matter development (30).…”
Section: Discussionmentioning
confidence: 75%
“…We speculate that stress exposure in the immature brain has an adverse effect on cerebral injury and/or development such that reduction in stress via MITP-type intervention enhances cerebral white matter development as measured by ADC and anisotropy. This is supported by recent experimental data in the immature brain that has emphasized the capacity of mild chronic stress to worsen brain injury (29). In addition, stress exposure increases hypothalamic-pituitary-adrenal (HPA) hormonal reactions resulting in altered cerebral white matter development (30).…”
Section: Discussionmentioning
confidence: 75%
“…71 We have shown that mild chronic stress during murine gestation sensitizes the neonatal brain to excitotoxic lesions in a manner comparable to systemic injection with cytokines. 18 Preliminary data show that administration of RU486, a glucocorticoid and progesterone receptor blocker, completely prevents the sensitizing effect of systemic IL-1b (Fig. 2), suggesting an involvement of the hypothalamo-pituitary-adrenal axis (and/or progesterone receptors) in the sensitizing effect of systemic inflammation.…”
Section: Glucocorticoidsmentioning
confidence: 88%
“…Substantial numbers of preclinical studies have demonstrated the sensitizing effects of gestational or neonatal systemic inflammation, gestational chronic mild maternal stress, and gestational hypoxia on perinatal excitotoxic or hypoxic-ischaemic lesions. [16][17][18][19][20][21] Genetic factors have also been shown to influence the developing brain's response to sensitizing factors. 22,23 Robust epidemiological studies, performed in preterm and term-born neonates, support a role for inflammation as a sensitizer.…”
Section: Concept Of Inflammation-induced Sensitizationmentioning
confidence: 99%
“…Quantification of mRNAs for NMDA receptor subunits showed no significant alterations in the expression of these receptors. Thus, changes in these receptors cannot explain the increased NMDA agonist toxicity, in contrast for instance to data from neonates born to dams subjected to chronic mild stress during pregnancy (24). This finding suggests that AUVL may alter NMDA receptor function downstream from receptor expression.…”
Section: Discussionmentioning
confidence: 85%